The relationship between management accounting implementation and business performance of Vietnamese small and medium enterprises (International Journal of Management and Sustainability, 2025)
The study examines the relationship between management accounting implementation and the business performance of Vietnamese small and medium enterprises. The quantitative study analyzed data collected from 259 Vietnamese small and medium enterprises using a convenient non-probability sampling method. Based on the evaluation of relevant domestic and foreign research, a model and research hypotheses are put forward to investigate the impact of management accounting applications on performance. Experts’ opinions guided the design and editing of the questionnaire, and we assessed its reliability using Cronbach’s alpha coefficient. The convergent and discriminant validity of the scales were evaluated by Exploratory Factor Analysis. Regression analysis using SPSS software to evaluate influence between factors in the proposed model. Analysis results show that management accounting implementation is positively influenced by business size, managers' awareness, level of competition, and accountants' competencies; implementation investment costs have a negative impact. Competitive pressure is the most influential factor motivating business managers to apply management accounting to their businesses to improve business efficiency. Business size significantly influences the application of management accounting, with small and medium-sized business models having the slightest impact. The implementation of management accounting positively affects performance. Therefore, the research provides evidence about current management accounting and enterprise business performance. The research has practical value for managers in expanding the application of management accounting in small and medium enterprises.